(untitled) (Journal of Economic Research & Business Administration, 2016)
The article explores the history of the global issues of environmental protection, conditionally subdivided into several stages, each of which is characterized by certain understanding of the relationship between ecology and economy. It considers historical periods of formation of sustainable development and «green» economy, presentsachronological summary of each stage. The authors give various interpretations of the concepts of «sustainable development» and «green» economy». The concept of «green» economy is still quite debatable, but its ideas are accepted by more and more countries and regions. The basic principles of transition to the «green» economy in Kazakhstan are revealed. «Green» economy is a new global course of innovative anti-crisis development of the world economy, which involves real improvements in the field of sustainable human well-being. It aims at building modern infrastructure and increasing comfort of living, implies massive reproduction of highly-paid jobs, facilitates the transition to the new principles of financing and taxation, revolutionizes education and science.